The Relationship between Hypertension and Dyslipidemia with Degree of Coronary Stenosis in Patients with Coronary Artery Disease at Abdoel Wahab Sjahranie Hospital in Samarinda - Maghfiroh, Qonita Yaumil; Sawitri, Endang; Hardianto, Djoen (Jurnal Kesehatan Pasak Bumi Kalimantan, 2025)
Coronary Heart Disease or Coronary Artery Diseae (CAD) is the leading cause of death in worldwide, including in Indonesia. CAD is caused by blockage of the coronary arteries, which a coronary angiography examination can confirm to assess the degree of stenosis. Hypertension and dyslipidemia are the main risk factors in patients with CAD. This study aims to analyze the relationship between hypertension and dyslipidemia with the degree of coronary stenosis in patients with CAD who undergo angiography at Abdoel Wahab Sjahranie Samarinda Hospital. This study is a type of analytic observational research with a cross-sectional approach. The data used in this study was from medical records. The study sample was 93 patients with CAD who underwent angiography at Abdoel Wahab Sjahranie Samarinda Hospital in 2022 and met the inclusion and exclusion criteria selected by purposive sampling. The result showed that the relationship between hypertension and the degree of coronary stenosis showed a p-value of 0.632 and a p-value of 0,034 for the relationship between dyslipidemia and the degree of coronary stenosis. The conclusion of this study is that hypertension has no relasionship with the degree of coronary stenosis and dyslipidemia has a significant relationship with the degree of coronary stenosis in patients with CAD who undergo angiography. Keywords:  Coronary Artery Disease, Hypertension, Dyslipidemia, Degree of Coronary Stenosis, Angiography